Managing the risk of violating human rights under industrial resettlement programs - Bussotti, L.; Maia, R. (Problems of Management in the 21st Century, 2017)
The purpose of this reflection is understanding what approaches towards human rights are applied in the case of industrial resettlement programs, and, to investigate what policy could be employed to better protect rights of people who experienced un-voluntary relocation event caused by industrial pressure in the context of Sub-Saharan Africa.